2021
DOI: 10.1111/jvim.16058
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐ictal magnetic resonance imaging characteristics in dogs with suspected idiopathic epilepsy

Abstract: Background: The pathophysiology of changes in magnetic resonance imaging (MRI) detected after a seizure is not fully understood. Objective: To characterize and describe seizure-induced changes detected by MRI. Animals: Eighty-one client-owned dogs diagnosed with idiopathic epilepsy. Methods: Data collected retrospectively from medical records and included anatomical areas affected, T1-, T2-weighted and T2-FLAIR (fluid-attenuated inversion recovery) appearance, whether changes were unilateral or bilateral, symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Additional support for thalamic involvement has recently been reported by Unger et al that found bilateral rotary saturation effects in the thalamus using phase-cycled stimulus-induced rotary saturation sequence in an Old English Bulldog with generalized tonic–clonic seizures ( 55 ). Even peri-ictal MRI changes have been found in parts of the thalamus in dogs ( 56 ). Network analysis of peri-ictal lesions has shown high correlation with cingulate lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Additional support for thalamic involvement has recently been reported by Unger et al that found bilateral rotary saturation effects in the thalamus using phase-cycled stimulus-induced rotary saturation sequence in an Old English Bulldog with generalized tonic–clonic seizures ( 55 ). Even peri-ictal MRI changes have been found in parts of the thalamus in dogs ( 56 ). Network analysis of peri-ictal lesions has shown high correlation with cingulate lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic epilepsy was diagnosed after exclusion of reactive seizure etiologies, along with cerebrospinal fluid analysis and either normal magnetic resonance imaging of the brain or abnormalities consistent with postictal brain pathology. 15 , 16 Structural epilepsy included vascular, neoplastic, inflammatory, traumatic, degenerative, or congenital diseases capable of contributing to epileptic seizure episodes, which were identified using some combination of cerebrospinal fluid analysis, magnetic resonance imaging, and necropsy examination. Reactive seizures were diagnosed if a metabolic etiology or intoxication was identified or strongly suspected based on historical information (such as exposure to a seizurogenic toxin, hepatic encephalopathy, hypertriglyceridemia, hypoglycemia, electrolyte disturbances, hyperthermia, or cerebral hypoxia).…”
Section: Methodsmentioning
confidence: 99%
“…Possible underlying etiologies for SE were categorized as IE, structural epilepsy, or reactive seizures. Idiopathic epilepsy was diagnosed after exclusion of reactive seizure etiologies, along with cerebrospinal fluid analysis and either normal magnetic resonance imaging of the brain or abnormalities consistent with postictal brain pathology 15,16 . Structural epilepsy included vascular, neoplastic, inflammatory, traumatic, degenerative, or congenital diseases capable of contributing to epileptic seizure episodes, which were identified using some combination of cerebrospinal fluid analysis, magnetic resonance imaging, and necropsy examination.…”
Section: Methodsmentioning
confidence: 99%
“…Except for a few genetic epilepsies, the causes of canine epilepsy are poorly understood. Although the introduction of the MRI as a diagnostic tool of epileptic dogs has disclosed a variety of structural and functional brain abnormalities in such animals (38,39,(132)(133)(134)(135)(136), this by itself does not explain the exact molecular causes of spontaneous recurrent seizures as observed in epilepsy. Furthermore, epileptic dogs, including those with "idiopathic" epilepsy, may have heterogeneous underlying pathologies, including subtle structural changes that cannot be identified on conventional visual inspection of brain MRI.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…In a recent peri-ictal MRI study in 81 dogs with suspected idiopathic epilepsy, the most common brain areas affected were the hippocampus (39/81), cingulate gyrus (33/81), and piriform lobes (32/81) ( 135 ). This may suggest that, similar to humans, the limbic system (or mesial temporal lobe) is particularly affected in epileptic dogs.…”
Section: Pathogenesis Of Epilepsy In Dogsmentioning
confidence: 99%